DEVELOPMENT AND ANALYSIS OF A MATHEMATICAL MODEL OF CARBON POLLUTION LEVEL ON KENYAN HIGHWAYS WITH HUGE EMBANKMENTS - Awino, John Otieno; Onyango, Thomas; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Carbon pollution on highways is attributed to major health problems experienced by those whostay along the highways. Most existing models developed by researchers have shown that COwhich is the cause of many diseases suffered by those who stay close to highways. However,most researches have shown lack of mechanistic understanding of how roadside barriers affectpollutant transport and transformation on and near roadways, especially under differentmeteorological conditions and barrier properties, for example highway embankment. In thisstudy we have therefore constructed a mathematical model incorporating embankment as aparameter. The black carbon concentration in the atmosphere along highways at different timescales will be simulated numerically using Finite Volume Method (FVM), with assumption thatpresence of embankment affects the physical parameters such as convection, Advection anddiffusion.